Analisis Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) Terhadap Efektivitas Penyuluhan dan Produktivitas Padi Sawah di Kecamatan Denpasar Timur - Zai, Vicarius Anugrah Jaya; Suardi, I Dewa Putu Oka (Universitas Galuh, 2025)
Digital transformation in agricultural extension is an important strategy for accelerating the dissemination of innovation and increasing the productivity of the agricultural sector. This study aims to analyze the use of information and communication technology (ICT) and its impact on the effectiveness of extension services and rice productivity in East Denpasar District. The research location was selected purposively, with a population of 529 farmers from Subak Temaga, Subak Padanggalak, and Subak Buaji, and a sample size of 53 individuals selected using proportional sampling techniques. Data collection methods included observation, interviews, and documentation using a questionnaire as an instrument. Data analysis was conducted descriptively and quantitatively using the SEM-PLS model. The results showed that the level of ICT utilization was moderate (64.64%), with the use of mobile phones, computers, televisions, and social media. The effectiveness of extension services was classified as high (68.03%), covering aspects of understanding, enjoyment, attitude change, social relations, and action. Rice productivity was categorized as moderate (63.01%), covering aspects of cultivation intensification, effective allocation of agricultural inputs, agricultural resource management, and production improvement. The SEM-PLS test shows that ICT has a positive effect on the effectiveness of extension services (O value = 0.685; p = 0.000 < 0.05), and the effectiveness of extension services acts as a mediator for productivity (O value = 0.689; p = 0.000 < 0.05). However, ICT does not have a direct effect on rice productivity (O value = 0.149; p = 0.125 > 0.05). These findings provide important insights for developing more effective agricultural extension strategies in the digital age.